The Effect Of Health Education On Personal Hygiene During Menstruation On The Behavior Of Female Adolescents At SMAN 1 Jombang, Jombang Regency - Sholikhah, Dwi Uswatun; Faizah, Rohmatul; Puspita, Enny (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Background: Neglect of reproductive health can cause reproductive tract infections and affect infertility and other reproductive diseases, in order to avoid reproductive diseases, knowledge of how to do proper Personal Hygiene is needed. This study aims to determine the Effect of Health Education About Personal Hygiene during Menstruation on the Behavior of Female Adolescents at SMAN 1 Jombang. Methods: This study used a Quasi Experimental design with a one group pretest-posttest design approach. The sample in this study was 65 female students in grades X1,2,3,4 with a total sampling technique. The research instrument used a questionnaire using the Wilcoxon Signed Rank Test statistical test. Results: The results showed that before being given health education, 36 female respondents (55%) behaved negatively and 29 respondents (45%) behaved positively. After being given health education, all female students behaved positively, 65 respondents (100%). The results of the statistical test obtained a p value = 0.000 (0.05) which means that there is an Influence of Health Education About Personal Hygiene During Menstruation on the Behavior of Female Adolescents at SMAN 1 Jombang Conclusion: Providing health education about personal hygiene during menstruation has an impact on increasing behavior in maintaining reproductive hygiene